2015
DOI: 10.1002/cbic.201500258
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Epimers C2 and C2a in the Gentamicin C Complex

Abstract: Gentamicin is a broad-spectrum aminoglycoside antibiotic widely used to treat life-threatening bacterial infections. The gentamicin C complex consists of gentamicin C1, gentamicin C1a, and epimers gentamicin C2 and gentamicin C2a. At present there is a generally accepted pathway of gentamicin biosynthesis, except for detailed understanding of the epimerization process involving gentamicins C2 and C2a. Here we have investigated the biosynthesis of these epimers. JI-20B-an intermediate in the gentamicin biosynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…Importantly, when GenB4-GenB2 were combined to catalyze (3), the reaction efficiency was remarkably improved and produced the deamination product, 6′-deamino-6′-oxoverdamicin (1). Hence, we concluded that (2) was verdamicin C2a and that (3) was verdamicin C2 [21].…”
Section: Genb4 Catalyzes Sisomicin (4) To Gentamicin C1a (9)mentioning
confidence: 75%
“…Importantly, when GenB4-GenB2 were combined to catalyze (3), the reaction efficiency was remarkably improved and produced the deamination product, 6′-deamino-6′-oxoverdamicin (1). Hence, we concluded that (2) was verdamicin C2a and that (3) was verdamicin C2 [21].…”
Section: Genb4 Catalyzes Sisomicin (4) To Gentamicin C1a (9)mentioning
confidence: 75%
“…The production of gentamicin X2 from A2 involves four enzymes: oxidoreductase, transaminase, and two methyltransferases [ 6 ]. X2 can also be transformed into JI-20A by C-6ʹ dehydrogenase and transaminase [ 7 9 ]. Moreover, GenK is the methyltransferase of C-6ʹ in gentamicin, and gen K disruption generates a gentamicin C1a-overproducing strain [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the key steps in the biosynthesis of gentamicin C components have been elucidated in previous work ( Figure 2): genK is an S-Adenosyl methionine (SAM) dependent methylation gene and is responsible for C-6' methylation [11,12]; genP is thought to be responsible for 3', 4' double dehydroxylation [13,14]; genQ is related to Gentamicin C-6' dehydrogenation [15]; genB1 catalyzes the transformation of G418 to JI-20B and X2 to JI-20A [16]; genB2 involves in the epimerization of gentamicin C2 and C2a in vitro [16]; and genL is reported to be responsible for converting C1a to C2b and C2 to C1 of Micromonospora echinospora ATCC15835 [17]. Figure 2.…”
Section: Gentamicin C1 C1a C2 C2a C2bmentioning
confidence: 99%
“…Previously, our team constructed an M. purpurea strain GK1101 to increase the titers of C1a [11], where C1 metabolic flux was blocked by inactivating the genK pathway ( Figure 2). However, this strain still produced a small amount of gentamicin C2b and an extra separation step is required to Most of the key steps in the biosynthesis of gentamicin C components have been elucidated in previous work ( Figure 2): genK is an S-Adenosyl methionine (SAM) dependent methylation gene and is responsible for C-6' methylation [11,12]; genP is thought to be responsible for 3', 4' double dehydroxylation [13,14]; genQ is related to Gentamicin C-6' dehydrogenation [15]; genB1 catalyzes the transformation of G418 to JI-20B and X2 to JI-20A [16]; genB2 involves in the epimerization of gentamicin C2 and C2a in vitro [16]; and genL is reported to be responsible for converting C1a to C2b and C2 to C1 of Micromonospora echinospora ATCC15835 [17]. Most of the key steps in the biosynthesis of gentamicin C components have been elucidated in previous work ( Figure 2): genK is an S-Adenosyl methionine (SAM) dependent methylation gene and is responsible for C-6' methylation [11,12]; genP is thought to be responsible for 3', 4' double dehydroxylation [13,14]; genQ is related to Gentamicin C-6' dehydrogenation [15]; genB1 catalyzes the transformation of G418 to JI-20B and X2 to JI-20A [16]; genB2 involves in the epimerization of gentamicin C2 and C2a in vitro [16]; and genL is reported to be responsible for converting C1a to C2b and C2 to C1 of Micromonospora echinospora ATCC15835 [17].…”
Section: Genlmentioning
confidence: 99%